The antecedents of purchase intention of local brands: A systematic literature review - Septiani, Emilia; Kerti Yasa, Ni Nyoman; Ekawati, Ni Wayan; Sukaatmadja, I Putu Gde (Asian Management and Business Review, 2024)
This study reviews and summarizes empirical findings on the determinants of local brand purchase intentions over the past five years. It aims to provide a comprehensive understanding of the literature for future researchers by using a systematic literature review approach to identify key influencing factors. A total of 34 empirical research articles from 2018 to 2022 were reviewed. The dominant theory applied was brand management, found in nine articles (26%), followed by social identity theory in four articles (11.8%), consumer behavior in three articles (8.9%), and country of origin in two articles (5.9%). Most studies focused on emerging or developing countries. The review identified six main theories used to explain local brand purchase intentions: brand management, consumer behavior, consumer culture positioning, country of origin, social identity, and the theory of reasoned action. The findings highlight a strong correlation between these theories and the likelihood of purchasing local brands, though results varied. Further research is needed to understand the complex interplay of these factors fully.